Talazoparib plus enzalutamide in men with first-line metastatic castration-resistant prostate cancer (TALAPRO-2): a randomised, placebo-controlled, phase 3 trial - Agarwal, Neeraj; Azad, Arun A; Carles, Joan; Fay, Andre P; Matsubara, Nobuaki; Heinrich, Daniel; Szczylik, Cezary; De Giorgi, Ugo; Young Joung, Jae; Fong, Peter C C; Voog, Eric; Jones, Robert J; et al. (The lancet, 2023)
Background - Co-inhibition of poly(ADP-ribose) polymerase (PARP) and androgen receptor activity might result in antitumour efficacy irrespective of alterations in DNA damage repair genes involved in homologous recombination repair (HRR). We aimed to compare the efficacy and safety of talazoparib (a PARP inhibitor) plus enzalutamide (an androgen receptor blocker) versus enzalutamide alone in patients with metastatic castration-resistant prostate cancer (mCRPC). - Methods - TALAPRO-2 is a randomised, double-blind, phase 3 trial of talazoparib plus enzalutamide versus placebo plus enzalutamide as first-line therapy in men (age ≥18 years [≥20 years in Japan]) with asymptomatic or mildly symptomatic mCRPC receiving ongoing androgen deprivation therapy. Patients were enrolled from 223 hospitals, cancer centres, and medical centres in 26 countries in North America, Europe, Israel, South America, South Africa, and the Asia-Pacific region. Patients were prospectively assessed for HRR gene alterations in tumour tissue and randomly assigned (1:1) to talazoparib 0·5 mg or placebo, plus enzalutamide 160 mg, administered orally once daily. Randomisation was stratified by HRR gene alteration status (deficient vs non-deficient or unknown) and previous treatment with life-prolonging therapy (docetaxel or abiraterone, or both: yes vs no) in the castration-sensitive setting. The sponsor, patients, and investigators were masked to talazoparib or placebo, while enzalutamide was open-label. The primary endpoint was radiographic progression-free survival (rPFS) by blinded independent central review, evaluated in the intention-to-treat population. Safety was evaluated in all patients who received at least one dose of study drug. This study is registered with ClinicalTrials.gov (NCT03395197) and is ongoing. - Findings - Between Jan 7, 2019, and Sept 17, 2020, 805 patients were enrolled and randomly assigned (402 to the talazoparib group and 403 to the placebo group). Median follow-up for rPFS was 24·9 months (IQR 21·9-30·2) for the talazoparib group and 24·6 months (14·4-30·2) for the placebo group. At the planned primary analysis, median rPFS was not reached (95% CI 27·5 months-not reached) for talazoparib plus enzalutamide and 21·9 months (16·6-25·1) for placebo plus enzalutamide (hazard ratio 0·63; 95% CI 0·51-0·78; p<0·0001). In the talazoparib group, the most common treatment-emergent adverse events were anaemia, neutropenia, and fatigue; the most common grade 3-4 event was anaemia (185 [46%] of 398 patients), which improved after dose reduction, and only 33 (8%) of 398 patients discontinued talazoparib due to anaemia. Treatment-related deaths occurred in no patients in the talazoparib group and two patients (<1%) in the placebo group. - Interpretation - Talazoparib plus enzalutamide resulted in clinically meaningful and statistically significant improvement in rPFS versus standard of care enzalutamide as first-line treatment for patients with mCRPC. Final overall survival data and additional long-term safety follow-up will further clarify the clinical benefit of the treatment combination in patients with and without tumour HRR gene alterations. - Funding - Pfizer.